Successful treatment of Depot Medroxyprogesterone acetate-related vaginal bleeding improves continuation rates in Adolescents. (2006) - Rager, Kristin M.; Fowler, Amy; Omar, Hatim A.
Abstract : High discontinuation rates for depot medroxyprogesterone acetate (DMPA) in adolescents may contribute to the number of unintended pregnancies. Many cite vaginal bleeding as a reason for discontinuing DMPA use. In this study, we attempted to determine if treating DMPA-associated vaginal bleeding with monophasic oral contraceptive pills (OCP) raised continuation rates. A total of 131 patients who reported vaginal bleeding while on DMPA were included in this study and 83 were treated with monophasic OCP. Of those who received OCP, 38.7% reported that vaginal bleeding stopped completely, 51.8% reported that vaginal bleeding stopped temporarily, and 6.0% reported no change. Overall, 94% of enrolled patients who received OCP as a treatment for DMPA-associated vaginal bleeding continued DMPA use. Our findings indicate that vaginal bleeding due to DMPA can be successfully treated, leading to improvement in continuation rates.